Orthodontic movement of teeth with short root anomaly: should it be avoided, faced or ignored? - Jose Valladares Neto; José Rino Neto; João Batista de Paiva (Dental Press Editora, 2013)
INTRODUCTION: Short Root Anomaly (SRA) is an uncommon disease and a challenge for orthodontic treatment as it tends to increase the risk of root resorption. OBJECTIVE: Assess the current status of the diagnosis, etiology and orthodontic management of teeth with SRA, and present case reports. METHOD: A literature review was carried out in PubMed, SciELO, LILACS, Scopus and Web of Science databases. RESULTS: A differential diagnosis of SRA should be conducted for teeth with incomplete root formation, external apical root resorption, dentin dysplasia type I and post dental trauma root hypoplasia. SRA is genetically determined and orthodontic movement requires changes in clinical and radiographic management in order to restrict damage. CONCLUSION: Orthodontic movement of teeth with SRA is contraindicated in extreme cases, only. Caution at all stages could minimize attachment loss and lead to long-term stability.